2011
DOI: 10.1088/0960-1317/21/12/125003
|View full text |Cite
|
Sign up to set email alerts
|

Porous inorganic–organic hybrid material by oxygen plasma treatment

Abstract: In this paper, we present the pore formation on inorganic-organic hybrid material, ORMOCER © , by reactive ion etching. ORMOCERs are composed of inorganic backbone where organic side groups are attached by cross-linking. Etching of ORMOCER in oxygen plasma generates porous materials with different pore sizes depending on the etching parameters. In addition to planar films, this pore formation process is applicable to micro and nanostructures. Characteristics of porous materials are evaluated by contact angle m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…42 We have recently studied the hydrophilization and pore formation process of ORMOCOMP by an oxygen plasma process using a different oxygen plasma process (reactive ion etching). 43 In that study, we found that the contact angles of all but the most clearly porous samples recovered to around 45 in three weeks, while the strongly porous samples retained complete wetting during that period.…”
Section: H Ormocompmentioning
confidence: 76%
See 1 more Smart Citation
“…42 We have recently studied the hydrophilization and pore formation process of ORMOCOMP by an oxygen plasma process using a different oxygen plasma process (reactive ion etching). 43 In that study, we found that the contact angles of all but the most clearly porous samples recovered to around 45 in three weeks, while the strongly porous samples retained complete wetting during that period.…”
Section: H Ormocompmentioning
confidence: 76%
“…The oxygen plasma treated samples had contact angles of around 50 after 100 days, consistent with the less porous samples of our previous study. 43 The nitrogen plasma treated samples had recovered completely to around 70 during 100 days. Compared with our previous study, 43 we do not find as stable hydrophilization due to the fact that the samples of this study are nonporous.…”
Section: H Ormocompmentioning
confidence: 98%
“…The Ormocomp® (Micro Resist Technology, Berlin, Germany) pillars were fabricated by UV‐embossing27 and plasma treatment 28. The pillar structures were first etched into silicon as described above and then transferred into polydimethylsiloxane (PDMS; Sylgard 184, Dow Corning, Midland, MI) by casting.…”
Section: Methodsmentioning
confidence: 99%
“…Polymer-like behavior enables for example spin coating and patterning by UV-embossing but it has problems in residual layer that prevents the fabrication of many microstructures [10]. ORMOCOMP ® channels have been shown to be free of fouling, as evidenced by stable migration times, which indicate that there are no hydrophobic or electrostatic interactions between ORMOCOMP ® and positively charged proteins [11,12]. ORMOCOMP ® has been utilized in cell growth platforms, by 3D two-photon polymerization [7][8][9].…”
Section: Ormocompmentioning
confidence: 99%
“…Due to its low shrinkage during curing, ORMOCOMP ® is very well suited for the replication of small features [10]. In addition, nanoscale pores can be formed in ORMOCOMP ® though the use of oxygen plasma [11]. The organic component is selectively removed, leaving an oxide skeleton with 10-100 nm pores.…”
Section: Ormocompmentioning
confidence: 99%